Development of Android application for MOSFET modeling and analysis - Hong, Xinyu (Nanyang Technological University, 2024)
In this study, an Android application for calculating MOSFET scattering parameters was developed to address the problems encountered by existing electronicdesign automation (EDA) tools in obtaining MOSFET parameters quickly and conveniently, especially for electronic students who require such auxiliary tools. This application simplifies the complex calculation process, allowing users to quickly obtain the necessary MOSFET scattering parameters by inputting relevant parameters. It can display the data calculation principles and steps according to user needs, effectively supporting the needs of circuit design and analysis. Meanwhile, in order to verify the accuracy and practicality of the application, this study chose MATLAB and Simpletex software as the main auxiliary testing tools. The test results show that the Android application has shown good performance in calculating MOSFET scattering parameters, demonstrating its potential in teaching and practical applications in the field of electronic design and helping students in this field to have a deeper understanding of critical concepts in circuit design.